Twelve tips for teachers to encourage student engagement in academic medicine. (July 2013) - Lawson McLean, Aaron; Saunders, Christopher; Velu, Prasad Palani; Iredale, John; Hor, Kahyee; Russell, Clark D.
<x xml:space="preserve">Abstract</x> Background: Recruitment of trainees into clinical academic medicine remains an area of concern across the globe, with clinical academics making up a dwindling proportion of the medical workforce. To date, few approaches have emphasised early medical student research involvement as a solution to the decline of the clinician-scientist. Aim and method: We identify 12 tips that all medical teachers can adopt to foster medical student participation in research and encourage student engagement with academic aspects of medicine throughout their time as an undergraduate. These recommendations are based on a comprehensive review of the international literature and our personal experience of research-focussed interventions and activities as medical students. Conclusion: Through these 12 tips, we provide a practical framework for enhancing medical student exposure to research at medical school. This has the potential to inspire and maintain student interest in the varied role of the clinical academic and could contribute to reversing the downward trend that has occurred in this field over recent times.